2020
DOI: 10.1021/acsmedchemlett.0c00063
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of BMS-986251: A Clinically Viable, Potent, and Selective RORγt Inverse Agonist

Abstract: Novel tricyclic analogues were designed, synthesized, and evaluated as RORγt inverse agonists. Several of these compounds were potent in an IL-17 human whole blood assay and exhibited excellent oral bioavailability in mouse pharmacokinetic studies. This led to the identification of compound 5, which displayed dose-dependent inhibition of IL-17F production in a mouse IL-2/IL-23 stimulated pharmacodynamic model. In addition, compound 5 was studied in mouse acanthosis and imiquimod-induced models of skin inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Compared to structure 2 (Figure ), the side chain amide nitrogen in the new series (compounds 3 – 7 ) is sterically hindered because it is attached to the tricyclic core, which could potentially alter or slow down metabolic processes such as N-dealkylation. Because the reverse amide series was a logical extension from our earlier tricyclic pyrrolidine series where the nitrogen atom was a part of the ring system, as illustrated in 1 , , a number of side chains studied earlier were re-examined here. Molecular modeling studies revealed that the trajectory of the side chains in both tricyclic pyrrolidine and reverse amide series point toward the RORγt polar pocket, consisting of a network of residues including Glu286, Leu287, Arg364, and Arg367.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to structure 2 (Figure ), the side chain amide nitrogen in the new series (compounds 3 – 7 ) is sterically hindered because it is attached to the tricyclic core, which could potentially alter or slow down metabolic processes such as N-dealkylation. Because the reverse amide series was a logical extension from our earlier tricyclic pyrrolidine series where the nitrogen atom was a part of the ring system, as illustrated in 1 , , a number of side chains studied earlier were re-examined here. Molecular modeling studies revealed that the trajectory of the side chains in both tricyclic pyrrolidine and reverse amide series point toward the RORγt polar pocket, consisting of a network of residues including Glu286, Leu287, Arg364, and Arg367.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As part of the screening process, we tested all newly synthesized compounds in both the GaL4-Luc reporter assay (GAL4) and a physiologically relevant IL-17-stimulated human whole blood (hWB) assay. Because the hWB EC 50 of 1 was 24 nM, 21 we required the EC 50 cutoff value of newly synthesized compounds to be ≤50 nM for further profiling. To assess MetStab, we measured the percent of parent remaining (% rem) following incubation with human, mouse, and rat liver microsomes, aiming for >90% recovery in these assays (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest the potential utility of ROR modulators as anti-diabetic and anti-obesity agents. On the other hand, multiple selective RORγ Inhibitors reduce T-helper cell 17 (Th17) responses as well as production of the proinflammatory cytokine IL-17, indicating the therapeutic potential of these molecules for autoimmune diseases, including rheumatoid arthritis, multiple sclerosis, psoriasis, and inflammatory bowel disease (Cyr et al, 2016;Pandya et al, 2018;Cherney et al, 2020;Harcken et al, 2021;Meijer et al, 2021). Pharmacological inhibition of RORγ also exerts potent anti-tumor activity in in vitro and/or in vivo models of castration-resistant prostate cancer (J.…”
Section: Modulating Casein Kinases (Cks)mentioning
confidence: 99%
“…We think that a statistical analysis of extensive structural information where one collectively examines protein-ligand contact interaction patterns may provide insight into this challenge. For this work, we studied 136 RORγ structures: 132 with one ligand (or ligand fragments) bound (100+ distinct ligands) from X-ray crystallography experiments ( Jin et al, 2010 ; Fujita-Sato et al, 2011 ; Fauber et al, 2013 ; Fauber et al, 2014 ; van Niel et al, 2014 ; Yang et al, 2014 ; Chao et al, 2015 ; Muegge et al, 2015 ; René et al, 2015 ; Santori et al, 2015 ; Scheepstra et al, 2015 ; Wang et al, 2015b ; Wang et al, 2015c ; Enyedy et al, 2016 ; Hirata et al, 2016 ; Hintermann et al, 2016 ; Marcotte et al, 2016 ; Olsson et al, 2016 ; Ouvry et al, 2016 ; Xue et al, 2016 ; Kallen et al, 2017 ; Kummer et al, 2017 ; Li et al, 2017 ; Noguchi et al, 2017 ; Carcache et al, 2018 ; Fukase et al, 2018 ; Gege et al, 2018 ; Gong et al, 2018 ; Kono et al, 2018 ; Narjes et al, 2018 ; Noguchi et al, 2018 ; Sasaki et al, 2018 ; Schnute et al, 2018 ; Shirai et al, 2018 ; Wang et al, 2018 ; Amaudrut et al, 2019 ; Duan et al, 2019 ; Hoegenauer et al, 2019 ; Kotoku et al, 2019 ; Lu et al, 2019 ; Marcoux et al, 2019 ; Sato et al, 2019 ; Strutzenberg et al, 2019 ; Tanis et al, 2019 ; von Berg et al, 2019 ; Yukawa et al, 2019 ; Zhang et al, 2019 ; Cherney et al, 2020 ; Duan et al, 2020 ; Gege et al, 2020 ; Harikrishnan et al, 2020 ; Jiang et al, 2020 ; Liu et al, 2020 ; Meijer et al, 2020 ;…”
Section: Introductionmentioning
confidence: 99%